Alkalinization with potassium bicarbonate improves glutathione status and protein kinetics in young volunteers during 21-day bed rest. Issue 2 (April 2019) - Biolo, Gianni; Di Girolamo, Filippo Giorgio; Heer, Martina; Sturma, Mariella; Mazzucco, Sara; Agostini, Francesco; Situlin, Roberta; Vinci, Pierandrea; Giordano, Mauro; Buehlmeier, Judith; Frings-Meuthen, Petra; Mearelli, Filippo; et al.
Summary: Background & aims: Physical inactivity is associated with lean body mass wasting, oxidative stress and pro-inflammatory changes of cell membrane lipids. Alkalinization may potentially counteract these alterations. We evaluated the effects of potassium bicarbonate supplementation on protein kinetics, glutathione status and pro- and anti-inflammatory polyunsaturated fatty acids (PUFA) in erythrocyte membranes in humans, during experimental bed rest. Methods: Healthy, young, male volunteers were investigated at the end of two 21-day bed rest periods, one with, and the other without, daily potassium bicarbonate supplementation (90 mmol × d −1 ), according to a cross-over design. Oxidative stress in erythrocytes was evaluated by determining the ratio between reduced (GSH) and oxidized glutathione (GSSG). Glutathione turnover and phenylalanine kinetics, a marker of whole body protein metabolism, were determined by stable isotope infusions. Erythrocyte membranes PUFA composition was analyzed by gas-chromatography. Results: At the end of the two study periods, urinary pH was 10 ± 3% greater in subjects receiving potassium bicarbonate supplementation (7.23 ± 0.15 vs. 6.68 ± 0.11, p < 0.001). Alkalinization increased total glutathione concentrations by 5 ± 2% (p < 0.05) and decreased its rate of clearance by 38 ± 13% (p < 0.05), without significantly changing GSH-to-GSSG ratio. After alkalinization, net protein balance in the postabsorptive state improved significantly by 17 ± 5% (p < 0.05) as well as the sum of n-3 PUFA and the n-3-to-n-6 PUFA ratio in erythrocyte membranes (p < 0.05). Conclusions: Alkalinization during long-term inactivity is associated with improved glutathione status, anti-inflammatory lipid pattern in cell membranes and reduction in protein catabolism at whole body level. This study suggests that, in clinical conditions characterized by inactivity, oxidative stress and inflammation, alkalinization could be a useful adjuvant therapeutic strategy.